Grouper fishery in the Northeastern Mediterranean: An assessment based on interviews on resource users. (January 2018) - Mavruk, Sinan; Saygu, İsmet; Bengil, Fethi; Alan, Vahit; Azzurro, Ernesto
Abstract: Groupers are important components of coastal ecosystems as well as a valuable resource for fisheries. Their populations are known to be decreasing throughout the world primarily due to over-exploitation. However, even the basic data for an effective management strategy is lacking. Interviews of a representative sample of 113 fishers in Turkey in the northeastern Mediterranean were conducted with specific questions regarding fishing gears, periods and areas as well as best day's catch and the sizes of fishes caught. Fishermen recognized Epinephelus marginatus, E. aeneus, E. costae, Hyporthodus haifensis, Mycteroperca rubra and Polyprion americanus distributed in the area. "Endangered" E. marginatus and "Near Threatened" E. aeneus were the dominant species of the grouper fishery. Based on best days' catch values and reported lengths of fish caught, the northern coasts of Iskenderun Bay were found to be important for both species. Demersal longliners, spearguns, traps, anglers and demersal trawlers were reported catching groupers in the study area. Artisanal fishermen, especially demersal longliners contributed the most to the grouper fishery. Fishing pressure were subject to seasonal fluctuations, with decreasing reported catches during summer when threatened groupers spawn. Finally, some critical aspects of fishery pressure were related to the removal of juveniles which may lead to reproduction loss. Highlights: E. aeneus and E. marginatus were reported as dominant in the Gulf of Iskenderun and Mersin. Demersal longliners are responsible of the most of grouper catches. Fishery pressure follows seasonal trends, with decreasing efforts during summer. Captures of juvenile and big ones may contribute to vulnerability of populations. Fisherman knowledge can help developing effective conservation and management plans.